Kekuatan Hukum Surat Perintah Perubahan Kerja dalam Kontrak Konstruksi: Studi Kasus Pembangunan Gardu Induk di Sumatera Bagian Tengah - Setiyawan, Iwan Arif; Pasaribu, David Mangara; Hikmahtiar, Rizal (SIGn Jurnal Hukum, 2024)
Variations in construction projects often lead to disputes, particularly concerning implementing change order instructions. To address this issue, this research aims to analyze the legal status of change order instructions in construction contracts in Indonesia, as well as the rights and obligations of the service provider (Contractor) related to the issuance of such instructions. This research employs a normative juridical approach with a case study of substation construction projects in Central Sumatra. Data sources include legislation, contract documents, and relevant legal literature. The research findings indicate that, although normatively based on the principle of freedom of contract and regulations on government procurement of goods/services, a change order instruction has a weak legal position without a contract addendum agreed upon by both parties. Furthermore, the Contractor has the right to negotiate changes and to reject instructions that do not follow procedure but is obligated to execute changes that have been agreed upon. The case analysis of the substation projects revealed that the absence of a firm clause regarding the status of change order instructions within the hierarchy of contract documents is the primary source of problems. Therefore, this research concludes that change order instructions require more comprehensive regulation within construction contracts to protect the parties’ rights and minimize the potential for disputes.